Proinflammatory signaling regulates voluntary alcohol intake and stress‐induced consumption after exposure to social defeat stress in mice. (7th June 2016) - Karlsson, Camilla; Schank, Jesse R.; Rehman, Faazal; Stojakovic, Andrea; Björk, Karl; Barbier, Estelle; Solomon, Matthew; Tapocik, Jenica; Engblom, David; Thorsell, Annika; Heilig, Markus
Abstract: Proinflammatory activity has been postulated to play a role in addictive processes and stress responses, but the underlying mechanisms remain largely unknown. Here, we examined the role of interleukin 1 (IL‐1) and tumor necrosis factor‐α (TNF‐α) in regulation of voluntary alcohol consumption, alcohol reward and stress‐induced drinking. Mice with a deletion of the IL‐1 receptor I gene (IL‐1RI KO) exhibited modestly decreased alcohol consumption. However, IL‐1RI deletion affected neither the rewarding properties of alcohol, measured by conditioned place preference (CPP), nor stress‐induced drinking induced by social defeat stress. TNF‐α signaling can compensate for phenotypic consequences of IL1‐RI deletion. We therefore hypothesized that double deletion of both IL‐1RI and TNF‐1 receptors (TNF‐1R) may reveal the role of these pathways in regulation of alcohol intake. Double KOs consumed significantly less alcohol than control mice over a range of alcohol concentrations. The combined deletion of TNF‐1R and IL‐1RI did not influence alcohol reward, but did prevent increased alcohol consumption resulting from exposure to repeated bouts of social defeat stress. Taken together, these data indicate that IL‐1RI and TNF‐1R contribute to regulation of stress‐induced, negatively reinforced drinking perhaps through overlapping signaling events downstream of these receptors, while leaving rewarding properties of alcohol largely unaffected. Abstract : Proinflammatory signaling has been suggested to play a role in alcohol intake and stress‐responses. Here, we show that mice with a genetic double deletion of interleukin 1 and TNF‐1 receptors decrease voluntary alcohol consumption and stress‐induced drinking following chronic social defeat stress. However, single deletion of either the interleukin 1 or TNF‐1 receptor results in modest or no effect on alcohol intake, suggesting that both receptors together are involved in regulation of alcohol consumption and stress‐induced drinking.